Cow’s Milk and Immune Function in the Respiratory Tract: Potential Mechanisms - Perdijk, Olaf; van Splunter, Marloes; Savelkoul, Huub F. J.; Brugman, Sylvia; van Neerven, R. J. Joost (Frontiers in Immunology, 2018)
During the last decades, the world has witnessed a dramatic increase in allergy prevalence. Epidemiological evidence shows that growing up on a farm is a protective factor, which is partly explained by the consumption of raw cow’s milk. Indeed, recent studies show inverse associations between raw milk consumption and asthma, hay fever and rhinitis. A similar association of raw milk consumption with respiratory tract infections is emerging. Similarly, controlled studies in infants with milk components like lactoferrin, MFGM and colostrum IgG have shown to reduce respiratory infections. However, for ethical reasons it is not possible to conduct controlled studies with raw milk in infants, so formal proof is lacking to date. Since viral respiratory tract infections and aeroallergen exposure in children may be causally linked to the development of asthma, it is of interest to investigate if milk components can modulate human immune function in the respiratory tract, and via which mechanisms. Inhaled allergens and viruses trigger local immune responses in the upper airways, both in nasal and oral lymphoid tissue (Waldeyer’s ring). The components present in raw cow’s milk are able to promote a local microenvironment in which mucosal immune responses are modified and the epithelial barrier is enforced. Additionally, such responses may also be triggered in the gut after exposure to allergens and viruses in the nasal cavity that become available in the GI tract after swallowing. However, these immune cells that come into contact with milk components in the gut must recirculate into the blood and home to the (upper and lower) respiratory tract in order to regulate immune responses locally. Expression of the tissue homing associated markers α4β7 and CCR9 and CCR10 on lymphocytes can be influenced by vitamin A and vitamin D3, respectively. As both of these are present in milk, we speculate that raw milk may influence homing of lymphocytes to the upper respiratory tract. This review focuses on the potential mechanisms via which milk or its components can influence immune function in the intestine and in the upper respiratory tract. Unravelling these complex mechanisms may contribute to the development of novel dietary approaches